Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.ihj.2018.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of epicardial fat quantification with severity of coronary artery disease: A study in Indian population

Abstract: ObjectiveWe studied the correlation of quantified epicardial fat with severity of coronary artery disease in patients [suspected cases of coronary artery disease (CAD)] referred for computed tomography (CT) coronary angiography and established cutoffs for epicardial fat volume (EFV) for the presence of CAD and obstructive CAD.MethodsA prospective cum retrospective cross-sectional observational study was carried out on 950 Indian subjects (suspected cases of CAD) who were referred for coronary CT in the year 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…There was a significant correlation between mean age and coronary calcium score between the CAD-present/-absent groups and significant CAD-present/-absent groups, similarly to the study done by Khurana et al . [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant correlation between mean age and coronary calcium score between the CAD-present/-absent groups and significant CAD-present/-absent groups, similarly to the study done by Khurana et al . [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, when the amount of epicardial fat increases, it becomes hypoxic and dysfunctional due to increased lipolysis and inflammation and alters hemostasis. As a result, it causes atherosclerosis and the formation of atherosclerotic plaque 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In many studies in the literature using epicardial fat volume, pericardial fat volume and epicardial adipose tissue thickness, a strong positive correlation was found between coronary artery stenosis and ischemic lesions and the amount of adipose tissue 13,15,19,21 . In the study conducted by Du et al, pericardial fat volume was found to be higher in patients with significant stenosis and ischemic lesions compared to those without 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Double-sector scanning (snapshot burst), large-scale scanning, or four-sector scanning (snapshot burst plus) were chosen, when the heart rate was >75 beats/min. 320 ml or 400 mg/L nonionic contrast medium (Onepak or Ultravist) was injected into the anterior elbow vein [11], and the flow rate was 4∼5 ml/s. e aortic root was scanned continuously with a delay of eight seconds and a scanning cycle of two seconds.…”
Section: Multislice Spiral Ct Coronary Angiographymentioning
confidence: 99%